Lifelong learning management for the urban poor: A case study of Khon Kaen city, Thailand - PIMCHANOK PAIREEPINAS; APISAK DHIRAVISIT; WILAIWATT GRISANAPUTI (Journal of Advanced Research in Social Sciences and Humanities, 2017)
Aim: This case study analysis aimed to examine the effects of Learning for life for the urban poor on investment and management education in Thailand. Corporations are the third most powerful entity in the United States.Methodology: through in-depth interviews and document analysisFindings: According to the results, public and private organizations must pitch in to fund the activities and projects crucial to the growth of the urban poor in neighborhoods bordering the rail line. Encourage learning at any age, not just during formal schooling. And the organizations in the public and private spheres working to improve people’s quality of life. And the possibilities for continuous education that are in line with the mandates of each institution.Novelty/Implications: The research will benefit the field of education as a whole, including institutions dedicated to lifelong education and groups catering to people of all ages.